CURRENT STATE OF DEVELOPMENT OF THE TRANSPORT INDUSTRY OF UKRAINE AND EFFECTIVENESS OF MECHANISMS OF FORMATION AND IMPLEMENTATION OF STATE POLICY - Maystro , S. V.; Krykhtina , Y. O (Theory and Practice of Public Administration, 2021)
The current state of development of the transport industry of Ukraine is determined. The state of development of the main sectors of the transport industry of Ukraine in modern conditions is described. A comprehensive analysis of the current state and existing problems of development of the transport sector of Ukraine in the light of threats and risks associated, including the coronary crisis. The effectiveness of the mechanisms of formation and implementation of the state policy of development of the transport industry of Ukraine is determined. It is emphasized that the transport industry has significant development potential due to the favorable geographical location of Ukraine. It is noted that the transport sector of Ukraine needs the formation and implementation of appropriate state policy in order to increase its competitiveness in terms of integration processes and existing challenges and threats.It is proved that the state policy should ensure the advanced pace of development of the transport sector in order to achieve sustainable (taking into account economic, social and environmental components) growth of the country’s gross domestic product and its active integration into the international transport market. It was found that in order to increase the efficiency of the country’s transport industry, it is necessary to implement a program of comprehensive renewal and modernization of transport, which will include a set of measures to ensure a favorable investment climate and a highly competitive environment. Ways to further implement the state transport strategy by identifying key issues, goals, principles and priorities of the transport sector in terms of national needs and interests, which will significantly improve its efficiency, sustainable development and welfare. It is proved that an important direction of further development of the country’s transport sector is the integration of Ukraine into the European Union, which requires the formation and implementation of appropriate state policy for the development of the transport sector.